2008
DOI: 10.1016/j.bone.2008.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of androgen receptor in bone reveals a lack of androgen anabolic action and inhibition of osteogenesis

Abstract: Androgens are anabolic hormones that affect many tissues, including bone. However, an anabolic effect of androgen treatment on bone in eugonadal subjects has not been observed and clinical trials have been disappointing. The androgen receptor (AR) mediates biological responses to androgens. In bone tissue, both AR and the estrogen receptor (ER) are expressed. Since androgens can be converted into estrogen, the specific role of the AR in maintenance of skeletal homoeostasis remains controversial. The goal of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
73
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(79 citation statements)
references
References 65 publications
6
73
0
Order By: Relevance
“…Between 12 and 32 weeks of age, mice apparently also do not experience significant cortical bone loss, in contrast to the decline in trabecular bone. (27,33) Despite the apparent preservation of cortical integrity, a lower ultimate force was needed for breaking ocy-ARKO bones compared with controls at 32 weeks of age. In line with our findings, previous models inactivating the AR at earlier stages of the osteoblast did not observe a significant difference in cortical structure, but mechanical properties were not documented.…”
Section: Discussionmentioning
confidence: 99%
“…Between 12 and 32 weeks of age, mice apparently also do not experience significant cortical bone loss, in contrast to the decline in trabecular bone. (27,33) Despite the apparent preservation of cortical integrity, a lower ultimate force was needed for breaking ocy-ARKO bones compared with controls at 32 weeks of age. In line with our findings, previous models inactivating the AR at earlier stages of the osteoblast did not observe a significant difference in cortical structure, but mechanical properties were not documented.…”
Section: Discussionmentioning
confidence: 99%
“…This outcome differs from the results reported by Chiang et al, 19 who observed a small reduction in the femoral cortical bone thickness in mice in which the exon 3 of the AR gene was deleted by similar osteocalcin promoter-activated Cre recombination. Taken together, the osteoblast targeted models by Notini et al, 20 Chiang et al 19 and us as well as the overexpression models by Wiren et al, 9,10 indicate that osteoblast precursors, but not mature osteoblasts or osteocytes, are the cells implementing the AR-mediated effects on periosteal apposition.…”
Section: Discussionmentioning
confidence: 70%
“…8 Overexpression of the AR in premature osteoblasts of male mice using the 3.6 kb type I collagen promoter has been shown to lead to an increase in periosteal bone formation and a reduction in endosteal bone formation, 9 whereas use of the 2.3 kb type I collagen promoter, expressed in mature osteoblasts, only reduced endosteal bone formation with no effect on the periosteum. 10 These different effects can be attributed, in addition to different stages of osteoblast maturation at which these promoters are active, to various patterns of their expression in bone tissue. The 2.3 kb type I collagen promoter is strongly expressed in endosteal osteoblasts and osteocytes, but not in the periosteum, 10,11 whereas the 3.6 kb type I collagen promoter has been shown to be active in the periosteum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, overexpression of the AR in osteoblasts from late in the matrix development and maturation stage using the 2 . 3 kb Col1a1 promoter has no effect on bone size as measured by periosteal circumference (Wiren et al 2008). Both AR transgenic models do, however, have a common phenotype of reduced formation at endocortical surfaces and increased trabecular bone volume as a result of reduced bone turnover (Wiren et al 2004(Wiren et al , 2008.…”
Section: Introductionmentioning
confidence: 99%